The Government of Disability in Dystopian Children’s Texts - Holdsworth, Dylan (Critical Approaches to Children's Literature, 2024)
Introduction: Worlds of Difference -- Chapter 1 -Goblin-ology: Eugenics and hysterisation in George MacDonald's The Princess and the Goblin (1872) -- Chapter 2 -"Lonely, tender, passionate heart": Melancholy and Isolation in Dinah Mulock Craik's The Little Lame Prince and his Traveling Cloak (1875) -- Chapter 3 -Building Beasties: Disability, Imperialism and Violence in William Golding's Lord of the Flies (1954) -- Chapter 4 -On the Fringes: John Wyndham's The Chrysalids (1955) and Technologies of the Self -- Chapter 5 -"A Perversion of Nature? How Exciting!": Tim Burton's Edward Scissorhands (1990), the Freak, the Monster and the Limits of Inclusion -- Chapter 6 -"Blind. Deaf. Disabled. Wheelchair": Community, History and Resistance in Jane Stemp's Waterbound (1995) -- Chapter 7 -"This Magic Keeps Me Alive, but it's Making Me Crazy!": Amputation, Madness and Control in Adventure Time (2009-2018) -- Chapter 8 -"Loss is Loss is Loss": Embodying the Family-as-Trauma in Julianna Baggott's Pure (2012).